2010
DOI: 10.1039/c002698k
|View full text |Cite
|
Sign up to set email alerts
|

Surface and interstitial Ti diffusion at the rutile TiO2(110) surface

Abstract: Diffusion of Ti through the TiO 2 (110) rutile surface plays a key role in the growth and reactivity of TiO 2 . To understand the fundamental aspects of this important process, we present an analysis of the diffusion of Ti ad-species at the stoichiometric TiO 2 (110) surface using complementary computational methodologies of density functional theory corrected for on-site Coulomb interactions (DFT + U) and a charge equilibration (QEq) atomistic potential to identify minimum energy pathways. We find that diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 45 publications
9
47
0
Order By: Relevance
“…This provides a more responsive description of the short-range bonding terms, and allows the variable-charge advantage of the QEq scheme to be retained 60 . We have found that the behaviour of oxygen within the Hallil model indicates 75 that the energetics of the QEq component underplay the costs of moving the charge both to and from the oxygen and in our calculations we keep the charge on all oxygens fixed to their bulk value of 1.26e -, with only the Ti ions able to transfer charge between themselves using the original charging self-80 energies 56 . This modification better reproduces the very small changes seen in oxygen charge found with DFT+U; further details can be found in refs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This provides a more responsive description of the short-range bonding terms, and allows the variable-charge advantage of the QEq scheme to be retained 60 . We have found that the behaviour of oxygen within the Hallil model indicates 75 that the energetics of the QEq component underplay the costs of moving the charge both to and from the oxygen and in our calculations we keep the charge on all oxygens fixed to their bulk value of 1.26e -, with only the Ti ions able to transfer charge between themselves using the original charging self-80 energies 56 . This modification better reproduces the very small changes seen in oxygen charge found with DFT+U; further details can be found in refs.…”
Section: Methodsmentioning
confidence: 99%
“…There is much interest in using the charge equilibration (QEq) scheme of Rappé and Goddard 54,55 for TiO 2 structures, in which the electronegativity of the ions is used to adjust the charge distribution in an adaptive manner. In our recent work, the 45 application of this approach to TiO 2 has been demonstrated via the QEq methodology 56 which allows charge transfer between ions to minimise the electrostatic energy Ees, whilst including contributions from the charging energies for each ion which takes a parabolic form: been achieved, the forces on the ions are used to move them in a standard minimisation or dynamics algorithm. The atomistic model includes short-range potentials to represent the covalent bonding which is significant for TiO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion processes in systems Ti, Cr, Al and other elements involved leading scientists [4], [5], [6], [7] of the world's.…”
Section: Methodsmentioning
confidence: 99%
“…13 Mulheran, et al demonstrated DFT+U and atomistic charge equilibration calculations give accordant results for surface and interstitial Ti diffusion at the rutile TiO2(110) surface. 17 Even though, influence of reductant defects at the TiO2(110)…”
mentioning
confidence: 99%